Smart Voice Assistants : an analysis of the opportunities for dutch grocery players from a consumer behavior perspective - Blaauw, Robbert Jan (2021)
This thesis dissertation presents an analysis of the opportunities for Smart Voice Assistants in the grocery retailing industry. Consumers are facing several costs in their grocery shopping activities which SVAs might alleviate while at the same time improving the overall grocery shopping experience for consumers. Grocery retailers count as the largest industry in the world and most of us deal with grocery shopping in our daily lives. The role of intermediaries for retailers between consumers and their products might present new challenges due to the rise of Smart Voice Assistants. Thus, it is necessary to analyze consumers' attitudes towards grocery shopping, as well as analyzing SVAs and what opportunities it may provide in the context of grocery shopping. A mixed-method approach of qualitative data from industry experts and a quantitative consumer study (n=169) was used. In addition, five potential features for SVA have been identified and tested among Dutch consumers. The attitudes of consumers in this study towards grocery shopping are negative, at the same time consumers recognize the benefits of SVAs for their shopping experience, as well as the identified features. However, SVA is not perceived as a technology that would make consumers switch to retailers that use SVA.